Pengembangan Sistem Point of Sale Menggunakan Framework Codeignetier Berbasis Web - Sukirno Sukirno; Heri Suhendar (Jurnal Algoritma, 2022)
The Point of Sale (POS) business management system is an application program that can facilitate all trading processes, but this system can only be installed on low-spec computers with a fairly complicated installation process. The problem is how to develop a POS application program into web programming so that it can be installed on all mainstream operating system products. The POS system that has been developed is a management system that can manage several important functions in business management, such as goods management, distributors, purchase transactions, sales transactions, purchase returns, sales returns, income, operational administration, to reports. The POS system is a web-based business management system using the PHP programming language with the codeigniter 3 framework, Apache web server and MySQL database. The research method uses action research, and the data collection method is in the form of interviews. The POS system was developed using the waterfall development model and designed using the UML design method, and tested using black box testing techniques. By going through the development process, the desktop-based POS application program was successfully developed into web programming using the PHP programming language with the CodeIgniter 3 framework and successfully developed to be installed on mainstream operating system products such as Windows, Linux and Macintosh.